PENGARUH PAJAK, UKURAN PERUSAHAAN, TUNNELING INCENTIVE, DAN PROFITABILITAS TERHADAP KEPUTUSAN TRANSFER PRICING (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR BASIC MATERIALS YANG LISTING DI BURSA EFEK INDONESIA PERIODE 2019 "“ 2021) - Yusnita, Erni (Jurnal KIAFE, 2023)
This research aims to test and analyze the influence of taxes, company size, tunneling incentives and profitability on transfer pricing decisions. The population in this study was 93 companies in the basic materials sector listed on the Indonesia Stock Exchange (BEI) for the 2019-2021 period. This research method is panel data regression using the Eviews version 12 tool. The results of this research show that partially the variables tax, company size and profitability have no influence on transfer pricing decisions, and the tunneling incentive variable has an influence on transfer pricing decisions. The research results show that simultaneously the variables tax, company size, tunneling incentive and profitability have no effect on transfer pricing decisions.